Optimization of tensile behavior of banana pseudo-stem (Musa acuminate) fiber reinforced epoxy composites using response surface methodology - Hassan, Mohamad Zaki; S.M., Sapuan; Roslan, Siti Amni; Abdul Aziz, Sa’ardin; Sarip, Shamsul (Elsevier, 2019)
Banana pseudo-stem fibers used as a reinforcing material in synthetic matrix polymers have offered various advantages as they are environmentally friendly, have relatively low density and are abundantly available. The main factors that influence the mechanical behavior of natural composites are fiber length, fiber content, and chemical treatment. This study optimized the blending parameters of banana pseudo-stem epoxy composites through response surface methodology (RSM) based on Box–Benhken design. The predicted tensile strength value for these composites as a function of an independent variable was obtained from the ANOVA statistical approach. The analysis of the results showed that fiber length, fiber content and sodium hydroxide variables significantly in 2 factors interaction (2FI) model terms. This model was used to determine the maximum tensile stress and it was closely agreement with experimental finding with the value of R2 = 0.9973. The optimum conditions for tensile strength were identified as fiber length 3.25 mm, sodium hydroxide content 5.45 (wt%), and fiber loading 29.86 (wt%). The maximum tensile strength of optimum banana pseudo-stem epoxy composite was increased by 22% over the epoxy-resin system.